217k views
4 votes
Solve the equation using the quadratic formulax^2+6x-2=0x=?

User Lvkz
by
6.6k points

1 Answer

1 vote

x^2\text{ + 6x - 2 = 0}

a = 1, b = 6, c = -1

Using the quadratic formula:


x\text{ = }\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}=\frac{-6\pm\sqrt[]{6^2-4\cdot1\cdot(-2)_{}}}{2\cdot1}=\frac{-6\pm\sqrt[]{36+8}}{2}=\frac{-6\pm\sqrt[]{44}}{2}=(-6\pm6.6332)/(2)
x_1=(-6+6.6332)/(2)=(0.6332)/(2)=0.3166
x_2=(-6-6.6332)/(2)_{}_{}=(-12.6332)/(2)=-6.3166

Answer:

x1 = 0.3166

x2 = -6.3166

User Alexander Bortnik
by
6.0k points